INTERACTIONAL ANALYSIS CATEGORIES (FIAC) FOR PEER OBSERVATION TO IMPROVE TEACHING AND LEARNING - Mohamed, Abdul Halim; Dzakiria, Hisham (Jurnal Inovasi Pendidikan, 2007)
Observing teachers especially experienced teachers can be a difficult task. Nevertheless, observation is an effective means to evaluate the effectiveness of teaching and learning practice of any course or program. Peer observation is one of the effective ways with relative ease. This paper discusses the findings of a study that involves three ESL (English as a Second Language) teachers at Changlon Secondary School in Kedah Malaysia. This study incorporates the use of Flanders? Interactional Analysis Category (FIAC) for Teacher Support Team (TST) program between Universiti Utara Malaysia (UUM) and the school. The paper begins first by explaining the involvement of the teachers and their feelings about peer observation. This paper then highlights teachers? feelings and perceptions towards FIAC as an alternative tool to observe and improve teaching effectiveness and how its use creates an awareness of the kind of teaching that takes place in their classrooms. The dogma of learner centered versus teachercentered teaching was evidently discussed. The paper concludes by providing ways to make the classrooms more learnercentred as opposed to the current practice of the teachers which are more teacher centered.